A wear-resistant graphene antistatic industrial coating and preparation method thereof

By adjusting the amount of epoxy resin and conductive filler, and adding inorganic filler and flame retardant, the obtained wear-resistant graphene anti-static industrial coating solves the problem of insufficient performance of existing coatings, significantly improving the multiple properties of the coating, so that it can show good durability and safety in various environments.

CN118813120BActive Publication Date: 2025-03-11ZHEJIANG HANGHUA SCREENS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411310996.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-03-11
Estimated Expiration
2044-09-20

AI Technical Summary

Technical Problem

The existing antistatic coatings have shortcomings in wear resistance, antistatic properties, UV aging resistance, flame retardant properties and corrosion resistance. They have many components and poor dispersion between raw materials, resulting in a decrease in coating performance over time.

Method used

Wear-resistant graphene anti-static industrial coatings are prepared by mixing epoxy resin, conductive filler, inorganic filler, hollow glass beads, curing agent, defoaming agent, leveling agent, dispersing agent, flame retardant, ultraviolet absorber and solvent. The types and dosages of each component are adjusted to improve the crosslinking density, conductive properties, ultraviolet light resistance, flame retardant and wear resistance of the coating.

Benefits of technology

The corrosion resistance, anti-static properties, ultraviolet aging resistance, flame retardant properties and wear resistance of the coating are significantly improved, so that the coating can maintain good performance under long-term use and ultraviolet irradiation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118813120B_ABST
    Figure CN118813120B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of graphene coatings, and specifically to a wear-resistant graphene antistatic industrial coating and a preparation method thereof. The present invention overcomes the problems of poor wear resistance, poor antistatic effect, poor resistance to ultraviolet light aging, poor flame retardant effect and poor corrosion resistance of graphene coatings. The present invention improves the crosslinking density of the coating by changing the type and amount of epoxy resin, so that the coating has better corrosion resistance; improves the conductivity of the coating by changing the content of conductive filler in the coating, so that the coating has better antistatic performance; reduces the damage of ultraviolet rays to the coating by changing the type and amount of ultraviolet absorber, and improves the resistance to ultraviolet light aging of the coating; improves the flame retardant performance of the coating by changing the type, amount and component ratio of the flame retardant; and makes the coating have more outstanding wear resistance by changing the amount of nano titanium dioxide, nano inorganic boron nitride and curing agent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of graphene coatings, in particular to a wear-resistant graphene antistatic industrial coating and a preparation method thereof. Background Art

[0002] When two different objects come into contact and rub against each other, the electrons of one object are transferred to the other object and become positively charged, while the other object gains electrons and becomes negatively charged, thus generating static electricity. In daily life, many materials are prone to static electricity accumulation during use, causing dust absorption, electric shock and other phenomena. For example, in the electronics industry, static electricity can greatly reduce the yield rate and service life of device production. During the manufacturing, production, assembly, testing, and handling of electronic components or systems, static electricity will accumulate on the human body, instruments, and electronic components. When these objects come into contact with each other to form a discharge path, the electronic components or systems will be damaged by static electricity discharge. In the petrochemical industry, oil products will generate static electricity by friction with the container or pipeline wall during the flow, pouring, loading and unloading, and stirring of oil products, causing objects to be charged. Static electricity may not only cause oil pollution, but once the energy of static electricity discharge is higher than the minimum ignition energy of oil products, it may even cause explosions and combustion accidents, posing a huge threat to safety.

[0003] Therefore, the research and development of antistatic coatings has become the focus of scientific research and industry. Antistatic coatings can give insulating materials certain conductive properties, so that the static charge generated on their surface can be quickly evacuated, thereby achieving the purpose of antistatic. Traditional antistatic coatings are mainly made by adding a variety of conductive fillers to the base resin. However, with the increasing market demand, their wear resistance and corrosion resistance have shown obvious shortcomings. In addition, the antistatic coatings in the prior art have many ingredients, the raw materials cannot be fully dispersed, and the filler receptivity is poor. As time goes by, the antistatic performance and UV aging resistance of the coating will decrease.

[0004] Graphene is a carbon atom in the form of sp 2 The hybrid orbitals form a hexagonal honeycomb lattice planar film, which is a two-dimensional material with only one atomic layer thickness, so it is also called single atomic layer graphite. The electron mobility of graphene at room temperature exceeds 15000cm² / V·s, which is higher than that of carbon nanotubes and silicon crystals. Its resistivity is only 10 6Ω·cm, which is lower than copper or silver, and is the material with the lowest resistivity in the world. Due to its excellent performance, graphene, as a new type of nanomaterial, shows great application potential in the field of coatings. However, how to effectively combine graphene with the coating matrix and improve its wear resistance and antistatic properties is a problem that needs to be solved urgently. Adding a single graphene to the coating still has its inherent defects. Graphene has poor dispersibility in the coating, and if graphene oxide with better dispersibility is used, its conductivity is relatively weak. Therefore, the present invention prepares a graphene composite filler to improve its conductivity.

[0005] Although the antistatic coatings prepared in the prior art have made certain progress, they still have some shortcomings. They have poor wear resistance and are easily worn when subjected to external forces; they have poor antistatic effect; they have poor resistance to ultraviolet light aging and will age and fall off under long-term sunlight exposure; they have poor flame retardant effect; they have poor corrosion resistance and are easily corroded by acids, alkalis and salts, which is not conducive to the protection of corrosive substrates.

[0006] Therefore, a wear-resistant graphene antistatic industrial coating and a preparation method thereof are proposed. Summary of the invention

[0007] The object of the present invention is to provide a wear-resistant graphene antistatic industrial coating and a preparation method thereof, wherein the wear-resistant graphene antistatic industrial coating is prepared by mixing epoxy resin, conductive filler, inorganic filler, hollow glass microspheres, curing agent, defoaming agent, leveling agent, dispersant, flame retardant, ultraviolet absorber and solvent. By changing the type and amount of epoxy resin, more cross-linking points are formed during the curing process, thereby increasing the cross-linking density of the coating, making the coating structure denser and improving the corrosion resistance of the coating; by changing the content of conductive filler in the coating, the dispersion performance of the conductive filler and the degree of cross-linking with the resin can be improved, thereby improving the antistatic performance of the coating; by changing the type and amount of ultraviolet absorber, the damage of ultraviolet rays to the coating is reduced, so that the coating can still maintain good appearance and performance under long-term ultraviolet irradiation; by changing the type, amount and component ratio of flame retardants, the flame retardants can form a protective layer, inhibit the chain reaction of free radicals or absorb heat during the combustion process, thereby delaying or preventing the combustion of the coating; by changing the amount of nano titanium dioxide, nano inorganic boron nitride and curing agent, the wear resistance of the coating is improved.

[0008] To achieve the above object, the present invention provides the following technical solutions:

[0009] On the one hand, the present invention provides a method for preparing a wear-resistant graphene antistatic industrial coating, wherein the wear-resistant graphene antistatic industrial coating is prepared by the following steps:

[0010] 50-80 parts of epoxy resin, 17-35 parts of conductive filler, 15-25 parts of inorganic filler and 15 parts of hollow glass microspheres are fully mixed to obtain a mixture; 1-3 parts of curing agent, 2 parts of defoaming agent, 1.5 parts of leveling agent, 2 parts of dispersant, 1-5 parts of flame retardant, 0.5-1.5 parts of ultraviolet absorber and 40 parts of solvent are added to the mixture, stirred evenly, and discharged to obtain a wear-resistant graphene antistatic industrial coating.

[0011] Preferably, the epoxy resin is one of epoxy resin E20, epoxy resin E42, epoxy resin E44, epoxy resin E51, and epoxy resin E52.

[0012] Preferably, the method for preparing the conductive filler comprises the following steps:

[0013] Preparation of graphene oxide: natural flake graphite and sodium nitrate are added to concentrated sulfuric acid and stirred for 35 minutes to obtain mixture one; the stirring temperature is 0°C; potassium permanganate is added to the mixture one and the stirring is continued for 60 minutes to obtain mixture two; the mixture two is heated to 30-40°C and the stirring is continued for 45 minutes to obtain heated mixture two; deionized water is added to the heated mixture two and the mixture is cooled to room temperature after reacting for 60 minutes to obtain mixture three; deionized water and 40wt% hydrogen peroxide aqueous solution are added to the mixture three to obtain a bright yellow solution; the bright yellow solution is centrifuged, washed, and dried to obtain the graphene oxide;

[0014] Preparation of the conductive filler: dissolving hexadecyltrimethylammonium bromide in a 1M hydrochloric acid solution to obtain a solute; adding the graphene oxide to the solute and ultrasonically dispersing for 30 minutes to obtain component one; cooling the component one to 0°C and adding pyrrole monomer and stirring for 10 minutes to obtain component two; using 1M hydrochloric acid to prepare a solution with a concentration of 20% FeCl3·6H2O and then slowly dripping it into the component two, reacting at 0°C for 9 hours to obtain a product; filtering the product, washing it, and drying it at 50°C for 12 hours to obtain the conductive filler.

[0015] Preferably, the inorganic filler is one or both of nano titanium dioxide and nano inorganic boron nitride.

[0016] Nano-titanium dioxide has good interfacial bonding with organic resin molecules due to its fine particle size, and can form a tight network structure with the resin, which helps to improve the strength and hardness of the coating and effectively resist external wear. Nano-titanium dioxide can form evenly distributed tiny particles in the coating, which can share part of the load when worn and slow down the wear rate of the coating. Nano-boron nitride particles act as "micro bearings" in the coating, which can reduce friction and wear and extend the service life of the coating.

[0017] Preferably, the curing agent is an isocyanate curing agent; and the defoaming agent is a 4430 defoaming agent.

[0018] Preferably, the leveling agent is cobalt cyclohexaneate; and the dispersant is polyacrylamide.

[0019] Preferably, the flame retardant is one or more of triphenyl phosphate, hexabromocyclododecane, and dimethyl methyl phosphate.

[0020] Preferably, the ultraviolet absorber is one or both of 2,2-dihydroxy-4,4-dimethoxybenzophenone-5,5-disulfonic acid and 2,5-dihydroxy-4-methoxybenzophenone.

[0021] Preferably, the solvent is prepared by compounding xylene and n-butanol in a mass ratio of 3:1-6:1.

[0022] Another aspect of the present invention provides a wear-resistant graphene antistatic industrial coating, wherein the raw materials for producing the wear-resistant graphene antistatic industrial coating include epoxy resin, conductive filler, curing agent, defoaming agent, leveling agent, dispersant, flame retardant, ultraviolet absorber, hollow glass beads and solvent; the wear-resistant graphene antistatic industrial coating is prepared by any one of the preparation methods described above; the wear-resistant graphene antistatic industrial coating is immersed in 10% HCl solution and 10% NaOH solution for 60 days and 58 days respectively and remains intact; in a salt spray corrosion test, the coating does not bubble or fall off; the surface resistance of the wear-resistant graphene antistatic industrial coating is 10 3 Ω; the gloss loss rate of the wear-resistant graphene antistatic industrial coating is 1.06%; the fire resistance time of the wear-resistant graphene antistatic industrial coating is 31.5min, the mass loss is 2.6g, and the carbonization volume is 7cm 3 ; The mass loss of the wear-resistant graphene antistatic industrial coating in the wear resistance test is 0.002g.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] 1. The present invention forms more cross-linking points during the curing process by changing the type and amount of epoxy resin, thereby improving the cross-linking density of the coating. The high cross-linking density makes the coating structure denser and can effectively block the penetration of corrosive media. The prepared wear-resistant graphene antistatic industrial coating is immersed in 10% HCl solution and 10% NaOH solution for 60 days and 58 days respectively without damage; in the salt spray corrosion test, the coating will not bubble or fall off, showing significantly improved corrosion resistance.

[0025] 2. The present invention can improve the dispersion performance of the conductive filler and the degree of cross-linking with the resin by changing the content of the conductive filler in the coating, thereby improving the conductivity of the coating. The surface resistance of the wear-resistant graphene antistatic industrial coating is only 10 3 Ω, showing significantly improved antistatic properties.

[0026] 3. The present invention converts ultraviolet rays into heat or other forms of energy by changing the type and amount of ultraviolet absorbers, thereby preventing ultraviolet rays from directly irradiating the coating surface and reducing the damage of ultraviolet rays to the coating, so that the coating can still maintain good appearance and performance under long-term ultraviolet irradiation. The gloss loss rate of the wear-resistant graphene antistatic industrial coating obtained is 1.06%, showing significantly improved resistance to ultraviolet aging.

[0027] 4. The present invention changes the type, dosage and composition ratio of the flame retardant, and utilizes the characteristics of the flame retardant that it can form a protective layer, inhibit the chain reaction of free radicals or absorb heat during the combustion process, thereby delaying or preventing the combustion of the coating. The wear-resistant graphene antistatic industrial coating obtained has a fire resistance time of 31.5 min, a mass loss of 2.6 g, and a carbonization volume of 7 cm 3 , showing significantly improved flame retardant properties.

[0028] 5. The present invention adds inorganic fillers nano titanium dioxide and nano inorganic boron nitride to the coating. Nano titanium dioxide can enhance the hardness and interfacial bonding strength of the coating, while nano boron nitride provides excellent wear resistance and high temperature stability. By changing the amount of nano titanium dioxide, nano inorganic boron nitride and curing agent, the obtained wear-resistant graphene antistatic industrial coating has more outstanding wear resistance, and its mass loss is 0.002g. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a graph showing the antistatic performance test results of the wear-resistant graphene antistatic industrial coating of Example 18 of the present invention. DETAILED DESCRIPTION

[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] See also Figure 1 The present invention provides a wear-resistant graphene antistatic industrial coating and a preparation method thereof, and the technical scheme is as follows:

[0032] The substance information involved in the present invention is as follows:

[0033] Sodium nitrate CAS: 7631-99-4; concentrated sulfuric acid CAS: 7664-93-9; potassium permanganate CAS: 7722-64-7; hydrogen peroxide CAS: 7722-84-1; hexadecyltrimethylammonium bromide CAS: 57-09-0; pyrrole CAS: 109-97-7; hydrochloric acid CAS: 7647-01-0; nano titanium dioxide CAS: 13463-67-7; nano inorganic boron nitride CAS: 10043-11-5; isocyanate CAS: 75-13-8; cobalt cyclohexane CAS: 61789-51-3; acrylamide CAS: 79-06-1; triphenyl phosphate CA S: 115-86-6; hexabromocyclododecane CAS: 25637-99-4; dimethyl methyl phosphate CAS: 813-78-5; 2,2-dihydroxy-4,4-dimethoxybenzophenone-5,5-disulfonic acid CAS: 143982-77-8; 2,5-dihydroxy-4-methoxybenzophenone CAS: 52811-37-4430 defoamer 7; epoxy resin E20, epoxy resin E42, epoxy resin E44, epoxy resin E51, epoxy resin E52 were all purchased from Laizhou Baichen Insulation Material Co., Ltd.; natural flake graphite was purchased from Qingdao Haida Graphite Co., Ltd.; purchased from Shanghai Zhengui New Material Technology Co., Ltd.

[0034] Example 1

[0035] Preparation of conductive filler:

[0036] Preparation of graphene oxide: Put a 500mL three-necked flask into a 0°C ice-water bath, add 1.8g of natural flake graphite, 0.9g of sodium nitrate and 70mL of concentrated sulfuric acid into the three-necked flask, stir and react for 35min to obtain mixture one; add 6g of potassium permanganate to the mixture one, stir in the ice-water bath for 60min, heat to 35°C and continue stirring and reacting for 90min to obtain mixture two; add 80mL of deionized water to the mixture two, react for 60min, and cool to room temperature to obtain mixture three; add 100mL of deionized water and 6mL of 40% hydrogen peroxide aqueous solution to the mixture three to obtain a bright yellow solution; centrifuge, wash and dry the bright yellow solution to obtain the graphene oxide;

[0037] Preparation of the conductive filler: dissolving hexadecyltrimethylammonium bromide in 150 mL of 1M hydrochloric acid solution to obtain a solute; adding 0.03 g of the graphene oxide to the solute and ultrasonically dispersing for 30 minutes to obtain component one; cooling the component one to 0°C, adding 1 mL of pyrrole monomer and stirring for 10 minutes to obtain component two; weighing 3.9037 g of FeCl3·6H2O, using 1M hydrochloric acid to prepare the FeCl3·6H2O into a 50 mL solution, and then slowly dropping it into the component two, reacting at 0°C for 9 hours to obtain a product; filtering the product, washing it, and drying it at 50°C for 12 hours to obtain the conductive filler.

[0038] Preparation of wear-resistant graphene antistatic industrial coatings:

[0039] 50 parts of epoxy resin E20, 17 parts of conductive fillers, 15 parts of inorganic fillers and 10 parts of hollow glass microspheres are fully mixed to obtain a mixture; 1 part of curing agent, 2 parts of defoaming agent, 1.5 parts of leveling agent, 2 parts of dispersing agent, 1 part of flame retardant, 0.5 parts of ultraviolet absorber and 40 parts of solvent are added to the mixture, stirred evenly, and discharged to obtain wear-resistant graphene antistatic industrial coating; 15 parts of inorganic fillers include 7 parts of nano titanium dioxide and 8 parts of nano inorganic boron nitride; the curing agent is isocyanate; the defoaming agent is 4430 defoaming agent; the leveling agent is cobalt cyclohexane acid; the dispersing agent is polyacrylamide; the flame retardant is a mixture of triphenyl phosphate, hexabromocyclododecane and dimethyl methyl phosphate in a ratio of 1:1:1; the ultraviolet absorber is 2,2-dihydroxy-4,4-dimethoxybenzophenone-5,5-disulfonic acid; the solvent is compounded by xylene and n-butanol in a mass ratio of 3:1-6:1.

[0040] Embodiment 2-10

[0041] Referring to the preparation method and parameter conditions of Example 1, the specific differences are shown in Table 1.

[0042] Table 1 Preparation conditions of Examples 2-10

[0043]

[0044] Example 11 Corrosion resistance test

[0045] Dry the prepared coating sample at room temperature for 5 days, then put it into a vacuum drying oven at HKTC for 3 hours, cool it to room temperature, seal the edges with paraffin, and immerse two-thirds of the coating sample in 10% HCl solution and 10% NaOH solution respectively. The longest immersion time without damage is used to indicate the acid and alkali resistance.

[0046] The prepared coating samples were placed in an airflow salt spray corrosion test chamber for 1000 hours, and then the samples were taken out to observe whether the coating had blistering, cracking, falling off, etc. to test the salt spray resistance of the coating; the results are shown in Table 2.

[0047] Table 2 Corrosion resistance test of Examples 1-10

[0048]

[0049] It can be seen from Table 2 that in Examples 1-5, as the epoxy value increases, the corrosion resistance of the coating gradually increases. Since the increase in epoxy value will increase the epoxy groups in the same mass of epoxy resin, these epoxy groups can form more cross-linking points during the curing process, thereby increasing the cross-linking density of the coating. The high cross-linking density makes the coating structure denser, which can effectively block the penetration of corrosive media and improve the corrosion resistance of the coating. In Example 5, the amount of epoxy resin used is insufficient, and defects and pores will be formed when the coating is covered on the surface of the substrate, which will become channels for the invasion of corrosive media and reduce the corrosion resistance of the coating; in Examples 5-10, as the amount of epoxy resin increases, the corrosion resistance of the coating shows a trend of first increasing and then maintaining stability. As the amount of epoxy resin increases, the crosslinking degree of the coating increases and the corrosion resistance increases. In Example 8, when 65 parts of epoxy resin E52 are added to the coating, the crosslinking degree of the coating reaches a stable state, forming a uniform and dense coating, thereby effectively blocking the penetration of corrosive media such as acids, alkalis and salts. It can be immersed in 10% HCl solution and 10% NaOH solution for 60d and 58d respectively without damage; the coating will not bubble or fall off in the salt spray corrosion test.

[0050] Example 12

[0051] The conductive filler was prepared according to the method of Example 1 above.

[0052] Preparation of wear-resistant graphene antistatic industrial coatings:

[0053] 65 parts of epoxy resin E52, 20 parts of conductive fillers, 15 parts of inorganic fillers, and 10 parts of hollow glass microspheres are fully mixed to obtain a mixture; 1 part of a curing agent, 2 parts of a defoaming agent, 1.5 parts of a leveling agent, 2 parts of a dispersant, 1 part of a flame retardant, 0.5 parts of an ultraviolet absorber, and 40 parts of a solvent are added to the mixture, stirred evenly, and the mixture is discharged to obtain a wear-resistant graphene antistatic industrial coating; the 15 parts of inorganic fillers include 7 parts of nano titanium dioxide and 8 parts of nano inorganic boron nitride; the curing agent is isocyanate; the defoaming agent is 4430 defoaming agent; the leveling agent is cobalt cyclohexane acid; the dispersant is polyacrylamide; the flame retardant is a mixture of triphenyl phosphate, hexabromocyclododecane, and dimethyl methyl phosphate in a ratio of 1:1:1; the ultraviolet absorber is 2,2-dihydroxy-4,4-dimethoxybenzophenone-5,5-disulfonic acid; and the solvent is compounded by xylene and n-butanol in a mass ratio of 3:1-6:1.

[0054] Examples 13-17

[0055] Referring to the preparation method and parameter conditions of Example 12, the specific differences are shown in Table 3.

[0056] Comparative Example 1

[0057] A wear-resistant graphene antistatic industrial coating was prepared according to the method of Example 12, except that the conductive filler was graphene oxide.

[0058] Comparative Example 2

[0059] A wear-resistant graphene antistatic industrial coating was prepared according to the method of Example 12, except that no conductive filler was added.

[0060] Example 18 Antistatic Performance Test

[0061] The antistatic property of the coating was determined by a surface resistivity tester. A thickness gauge was selected to measure the coating surface thickness. Based on the determined coating thickness, a TERA Ohmmeter TOM 600 (Kleinwachter, Germany) was used to measure the surface resistance of the coating; the results are shown in Table 3.

[0062] Table 3 Antistatic performance test of Examples 8, 12-17 and Comparative Examples 1-2

[0063]

[0064] From Table 3 and Figure 1It can be seen that in Examples 8, 12-17, as the amount of conductive filler increases, the surface resistivity of the coating decreases continuously. When the amount of conductive filler increases to a certain value, the surface resistance of the coating drops suddenly, which is called the percolation threshold. After that, it tends to be flat or even rises, which is related to the formation of a conductive network. In Examples 8-14, when the amount of conductive filler added is less than 28 parts, the surface resistance of the coating is large. This is because the conductive particles in the coating are isolated by the resin and cannot form a conductive network that allows electrostatic electrons to transmit to each other. In Example 15, when the amount of conductive filler added is 28 parts, the percolation threshold is reached. At this time, the antistatic performance of the coating obtained is the best, and the surface resistance is only 10 3 Ω; when the amount of conductive filler added is greater than 28 parts, in Examples 16-17, the resistance of the coating surface no longer decreases and even increases. This is because the agglomerated graphene particles cannot be effectively dispersed in the coating, resulting in discontinuity and defects in the conductive path, thereby reducing the antistatic performance of the coating. In Comparative Example 1, the conductive filler is composed only of graphene oxide, which has good dispersion performance, but insufficient conductivity, and the surface resistance of the coating obtained reaches 10 10 Ω; In comparative example 2, no conductive filler was added to the coating, resulting in a significant reduction in the antistatic ability of the coating, and the surface resistance reached 10 14 Ω.

[0065] Embodiment 19

[0066] The conductive filler was prepared according to the method of Example 1 above.

[0067] Preparation of wear-resistant graphene antistatic industrial coatings:

[0068] 65 parts of epoxy resin E52, 28 parts of conductive fillers, 15 parts of inorganic fillers, and 10 parts of hollow glass microspheres are fully mixed to obtain a mixture; 1 part of curing agent, 2 parts of defoaming agent, 1.5 parts of leveling agent, 2 parts of dispersing agent, 1 part of flame retardant, 0.8 parts of ultraviolet absorber and 40 parts of solvent are added to the mixture and stirred evenly, and the material is discharged to obtain a wear-resistant graphene antistatic industrial coating; 15 parts of inorganic fillers include 7 parts of nano titanium dioxide and 8 parts of nano inorganic boron nitride; the curing agent is isocyanate; the defoaming agent is 4430 defoaming agent; the leveling agent is cyclopentane Cobalt alkanoate; the dispersant is polyacrylamide; the flame retardant is a mixture of triphenyl phosphate, hexabromocyclododecane and dimethyl methyl phosphate in a proportion of 1:1:1; the ultraviolet absorber is 2,2-dihydroxy-4,4-dimethoxybenzophenone-5,5-disulfonic acid; the solvent is a compound of xylene and n-butanol in a mass ratio of 3:1-6:1; the ultraviolet absorber 2,2-dihydroxy-4,4-dimethoxybenzophenone-5,5-disulfonic acid is recorded as A; the ultraviolet absorber 2,5-dihydroxy-4-methoxybenzophenone is recorded as B.

[0069] Examples 20-29

[0070] Referring to the preparation method and parameter conditions of Example 19, the specific differences are shown in Table 4.

[0071] Comparative Example 3

[0072] A wear-resistant graphene antistatic industrial coating was prepared according to the method of Example 19, except that no ultraviolet absorber was added.

[0073] Example 30 UV light aging resistance test

[0074] Three samples of 150 mm × 100 mm were taken and tested according to the test method specified in Q / JLY J7110279. The test time was 1200 h. The gloss loss rate was calculated based on the gloss before and after the test. The results are shown in Table 4.

[0075] Table 4 UV aging resistance test of Examples 15, 19-29 and Comparative Example 3

[0076]

[0077] As shown in Table 4, when the UV absorbers A and B are used in combination, the UV aging resistance is the best. By absorbing UV rays, reducing the direct irradiation and damage of UV rays to the coating, and stably existing in the coating, the coating can be protected from UV damage. In Example 28, when 1.2 parts of UV absorbers A and B are added, the light loss rate of the obtained coating is only 1.06%; in Examples 15, 22, and 26, when the amount of UV absorber added is too small, its ability to absorb UV light is limited, and it cannot fully absorb and convert harmful UV energy, resulting in the direct irradiation of UV light on the coating surface, accelerating the photodegradation reaction, thereby affecting the UV aging resistance of the coating. Increasing the amount of UV absorber added can improve the UV aging resistance of the coating to a certain extent, but when the amount added exceeds a certain limit, the performance improvement is not obvious. In Examples 21, 25, and 29, the absorption capacity of the UV absorber reaches saturation, and increasing the amount added cannot further improve the absorption efficiency. In Comparative Example 3, no UV absorber was added to the coating, and the obtained coating had poor anti-UV aging performance, with a light loss rate of 5.42%. The coating could not maintain a good appearance under long-term ultraviolet irradiation.

[0078] Embodiment 31

[0079] The conductive filler was prepared according to the method of Example 1 above.

[0080] Preparation of wear-resistant graphene antistatic industrial coatings:

[0081] 65 parts of epoxy resin E52, 28 parts of conductive fillers, 15 parts of inorganic fillers, and 10 parts of hollow glass microspheres are fully mixed to obtain a mixture; 1 part of curing agent, 2 parts of defoaming agent, 1.5 parts of leveling agent, 2 parts of dispersant, 2 parts of flame retardant, 1.2 parts of ultraviolet absorber and 40 parts of solvent are added to the mixture and stirred evenly, and the material is discharged to obtain a wear-resistant graphene antistatic industrial coating; 15 parts of inorganic fillers include 7 parts of nano titanium dioxide and 8 parts of nano inorganic boron nitride; the curing agent is isocyanate Cyanate ester; the defoamer is 4430 defoamer; the leveling agent is cobalt cyclohexane; the dispersant is polyacrylamide; the flame retardant is a mixture of triphenyl phosphate, hexabromocyclododecane and dimethyl methyl phosphate in a proportion of 1:1:1; the ultraviolet absorber is a mixture of 2,2-dihydroxy-4,4-dimethoxybenzophenone-5,5-disulfonic acid and 2,5-dihydroxy-4-methoxybenzophenone; the solvent is a mixture of xylene and n-butanol in a mass ratio of 3:1-6:1.

[0082] Examples 32-45

[0083] Referring to the preparation method and parameter conditions of Example 31, the specific differences are shown in Table 5.

[0084] Table 5 Preparation conditions of Examples 32-45

[0085]

[0086] Comparative Example 4

[0087] A wear-resistant graphene antistatic industrial coating was prepared according to the method of Example 31, except that no flame retardant was added.

[0088] Example 46 Flame retardant performance test

[0089] Flame penetration and test - large plate burning method (GB / T15442.2-1995)

[0090] The base material is first-grade five-layer plywood 900mm×900mm×5mm, and the wet coating ratio of the paint is 500g / m 2 , test the fire resistance time (the fire resistance time is the time required for the back-fire surface temperature of the specimen to reach 220°C or for penetration to occur on the test plate under specified substrate and specific combustion conditions); first-level decorative fire retardant coating: fire resistance time ≥ 20min.

[0091] Coating fire retardancy classification test - small chamber method (GB / T15442.4-1995)

[0092] The base material is first-grade five-layer plywood 300mm×150mm×5mm, and the wet coating ratio of the paint is 250g / m 2; Test: 5mL chemical grade anhydrous ethanol, the cup edge is 25mm away from the substrate, ignite, close the door, and the flame goes out by itself; weigh to measure the mass loss (g), measure the carbonization length, width, and depth of the substrate to calculate the carbonization volume (cm 3 ); First-class decorative fire retardant coating: mass loss ≤5g, carbonization volume ≤15cm 3 The results are shown in Table 6.

[0093] Table 6 Flame retardant performance test of Examples 28, 31-45 and Comparative Example 4

[0094]

[0095] As shown in Table 6, in Example 32, when triphenyl phosphate, hexabromocyclododecane, and dimethyl methyl phosphate were compounded in a ratio of 1:1:1, the flame retardant performance of the coating was significantly better than that of Examples 34-45. When 3 parts of the flame retardant were added to the coating, the flame retardant performance was the best. At this time, the fire resistance time reached 31.5 min, the mass loss of the substrate was only 2.6 g, and the carbonization volume was as small as 7 cm 3 In Example 28, the amount of flame retardant added is too little, and the expected flame retardant effect cannot be achieved, so that the coating is easy to burn when encountering fire and cannot effectively protect the substrate; in Examples 28, 31-33, as the amount of flame retardant added increases, the flame retardant effect will first increase and then weaken. Too much flame retardant may cause the flame retardant to be unevenly distributed in the coating, forming lumps, which in turn reduces the flame retardant effect. In Comparative Example 4, no flame retardant was added to the coating. At this time, the coating has poor flame retardant performance, with a fire resistance time of only 20.3 minutes, a mass loss of 5.8g, and a large carbonization volume of 16cm 3 .

[0096] Embodiment 47

[0097] The conductive filler was prepared according to the method of Example 1 above.

[0098] Preparation of wear-resistant graphene antistatic industrial coatings:

[0099] 65 parts of epoxy resin E52, 28 parts of conductive filler, 15 parts of inorganic filler, and 10 parts of hollow glass microspheres are fully mixed to obtain a mixture; 2 parts of curing agent, 2 parts of defoaming agent, 1.5 parts of leveling agent, 2 parts of dispersant, 3 parts of flame retardant, 1.2 parts of ultraviolet absorber and 40 parts of solvent are added to the mixture and stirred evenly, and the material is discharged to obtain a wear-resistant graphene antistatic industrial coating; 15 parts of inorganic filler include 7 parts of nano titanium dioxide and 8 parts of nano inorganic boron nitride; the curing agent is Isocyanate; the defoamer is 4430 defoamer; the leveling agent is cobalt cyclohexane; the dispersant is polyacrylamide; the flame retardant is a mixture of triphenyl phosphate, hexabromocyclododecane and dimethyl methyl phosphate in a proportion of 1:1:1; the ultraviolet absorber is a mixture of 2,2-dihydroxy-4,4-dimethoxybenzophenone-5,5-disulfonic acid and 2,5-dihydroxy-4-methoxybenzophenone; the solvent is a mixture of xylene and n-butanol in a mass ratio of 3:1-6:1.

[0100] Examples 48-57

[0101] Referring to the preparation method and parameter conditions of Example 47, the specific differences are shown in Table 7.

[0102] Comparative Example 5

[0103] A wear-resistant graphene antistatic industrial coating was prepared according to the method of Example 47, except that no inorganic filler was added.

[0104] Comparative Example 6

[0105] A wear-resistant graphene antistatic industrial coating was prepared according to the method of Example 47, except that no curing agent was added.

[0106] Example 58 Wear resistance test

[0107] The measurement was carried out according to the rotating rubber grinding wheel method in GB / T1768-2006 Determination of abrasion resistance of paints and varnishes; the results are shown in Table 7.

[0108] Table 7 Wear resistance test of Examples 32, 47-57, and Comparative Examples 5-6

[0109]

[0110] As shown in Table 7, in Examples 32 and 47, as the amount of curing agent increases, the wear resistance of the coating will gradually increase. This is because the curing agent promotes the cross-linking reaction of the coating, making the coating structure more compact and firm, thereby enhancing the wear resistance of the coating; however, in Example 48, excessive curing agent usage will cause the coating to dry too fast, increase the internal stress of the coating, and easily produce cracks and peeling, which will reduce the wear resistance of the coating. The mass loss of the obtained coating reaches 0.006g. In Examples 49-52, as the content of nano titanium dioxide increases, the wear resistance of the coating will first increase and then stabilize, and may even cause a decrease in hardness due to excessive addition. The use of nano titanium dioxide and nano boron nitride in the coating can produce a synergistic effect. Nano titanium dioxide can enhance the hardness and interfacial bonding of the coating, while nano boron nitride provides excellent wear resistance and high temperature stability, further improving the wear resistance of the coating. In Example 53, 10 parts of nano titanium dioxide and 10 parts of nano boron nitride were added to the coating, and the mass loss of the obtained coating was only 0.002g, with the best wear resistance. In Comparative Example 5, no inorganic filler was added to the coating, and the mass loss reached 0.012g; in Comparative Example 6, no curing agent was added, and the mass loss of the obtained coating was 0.010g, with poor wear resistance.

[0111] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a wear-resistant graphene antistatic industrial coating, characterized in that: The wear-resistant graphene antistatic industrial coating is prepared by the following steps: 65 parts of epoxy resin, 28 parts of conductive filler, 20 parts of inorganic filler, and 15 parts of hollow glass microspheres are fully mixed to obtain a mixture; 2 parts of curing agent, 2 parts of defoaming agent, 1.5 parts of leveling agent, 2 parts of dispersant, 3 parts of flame retardant, 1.2 parts of ultraviolet absorber and 40 parts of solvent are added to the mixture and stirred evenly, and the mixture is discharged to obtain a wear-resistant graphene antistatic industrial coating; The epoxy resin is epoxy resin E52; the inorganic filler is obtained by mixing 10 parts of nano titanium dioxide and 10 parts of nano inorganic boron nitride; the ultraviolet absorber is obtained by compounding 2,2-dihydroxy-4,4-dimethoxybenzophenone-5,5-disulfonic acid and 2,5-dihydroxy-4-methoxybenzophenone; the curing agent is an isocyanate curing agent; the defoaming agent is 4430 defoaming agent; the leveling agent is cobalt cyclohexane acid; the dispersant is polyacrylamide; the flame retardant is triphenyl phosphate, hexabromocyclododecane and dimethyl methyl phosphate, and the ratio of the three is 1:1:1; the solvent is compounded by xylene and n-butanol in a mass ratio of 3:1-6:1; The preparation method of the conductive filler comprises the following steps: Preparation of graphene oxide: natural flake graphite and sodium nitrate are added to concentrated sulfuric acid and stirred for 35 minutes to obtain mixture one; the stirring temperature is 0°C; potassium permanganate is added to the mixture one and the stirring is continued for 60 minutes to obtain mixture two; the mixture two is heated to 30-40°C and the stirring is continued for 45 minutes to obtain heated mixture two; deionized water is added to the heated mixture two and the mixture is cooled to room temperature after reacting for 60 minutes to obtain mixture three; deionized water and 40wt% hydrogen peroxide aqueous solution are added to the mixture three to obtain a bright yellow solution; the bright yellow solution is centrifuged, washed, and dried to obtain the graphene oxide; Preparation of the conductive filler: dissolving hexadecyltrimethylammonium bromide in a 1M hydrochloric acid solution to obtain a solute; adding the graphene oxide to the solute and ultrasonically dispersing for 30 minutes to obtain component one; cooling the component one to 0°C and adding pyrrole monomer and stirring for 10 minutes to obtain component two; using 1M hydrochloric acid to prepare a solution with a concentration of 20% FeCl3·6H2O and then slowly dripping it into the component two, reacting at 0°C for 9 hours to obtain a product; filtering the product, washing it, and drying it at 50°C for 12 hours to obtain the conductive filler.

2. A wear-resistant graphene antistatic industrial coating, characterized in that: The raw materials for producing the wear-resistant graphene antistatic industrial coating include epoxy resin, conductive filler, inorganic filler, hollow glass microspheres, curing agent, defoaming agent, leveling agent, dispersant, flame retardant, ultraviolet absorber and solvent; the wear-resistant graphene antistatic industrial coating is prepared by the preparation method described in any one of claim 1; the wear-resistant graphene antistatic industrial coating is immersed in 10% HCl solution and 10% NaOH solution for 60 days and 58 days respectively and remains intact, and the coating does not bubble or fall off in the salt spray corrosion test; the surface resistance of the wear-resistant graphene antistatic industrial coating is 10 3 Ω; the gloss loss rate of the wear-resistant graphene antistatic industrial coating is 1.06%; the fire resistance time of the wear-resistant graphene antistatic industrial coating is 31.5min, the mass loss is 2.6g, and the carbonization volume is 7cm 3 ; The mass loss of the wear-resistant graphene antistatic industrial coating in the wear resistance test is 0.002g.

Citation Information

Patent Citations

  • Indoor coating with sound absorption function and preparation method of indoor coating

    CN105505077A

  • Flame-resistant waterproof paint for high-speed rail

    CN106280966A

  • Graphene oxide preparation process

    CN106744928A

  • Wearing-resistant double-component graphene anti-corrosion coating

    CN110183934A

  • Preparation method of nano titanium dioxide modified hexagonal boron nitride modified coating

    CN113388311A